The Oxford handbook of meaningful work - Yeoman, Ruth, 1964-; Bailey, Catherine; Madden, Adrian; Thompson, Marc, 1962- (Oxford handbooks online., 2019)
This handbook examines the concept, practices, and effects of meaningful work in organisations and beyond. Taking an interdisciplinary approach, it reflects diverse scholarly contributions from philosophy, political theory, psychology, sociology, organisational studies, and economics.